Human Resource Management Practices and Organizational Citizenship Behaviour: The Moderating Role of Value-Based Leadership (Journal of Asian Development Studies, 2023)
Organizational Citizenship Behavior (OCB) has captured researchers’ attention for decades as it results in a higher level of organizational performance and productivity. Existing literature posits that Human Resource Management (HRM) practices and leadership play an important role in developing organizational citizenship behavior among employees. The purpose of the present research is to examine the impact of HRM practices and OCB. Further, it investigates the moderating role of value-based leadership between HRM practices and OCB. 411 samples were collected from academics and management staff/faculty members working in the management cadre or public sector grades 16-22, working in higher education institutes of Lahore. Multiple regression analyses using SPSS were performed to test the hypotheses of the present research. The findings show that HRM practices and value-based leadership are strongly related to OCB. Further, value-based leadership significantly moderated the relationship between HRM and OCB. This study provides a valuable framework for HR managers, educationists, and policymakers to enhance the effectiveness of value-based leadership in their organizations. Although the HRM-OCB relationship has been studied extensively, the literature on the importance of value-based leadership in such a relationship is relatively absent. This is the first study that examined the role of value-based leadership in the HRM-OCB relationship, filling a clear gap in the literature.